Leading Tanzanian Women in Financial Services : An Examination of Gender Equality in Tanzania’s Financial Services Sector - International Finance Corporation (World Bank, Washington, DC, 2022)
There is a strong business and economic case for increasing women’s representation in companies’ leadership, globally, and especially in Africa. In 2019, the International Labor Organization (ILO) conducted a worldwide survey on the impact of gender diversity initiatives on 13,000 enterprises. In the study, ILO found that approximately 90 percent of companies track the quantitative impact of gender diversity initiatives around promoting women in management, and of those nearly 74 percent saw an increase in profits of between 5 and 20 percent. Given how critical the financial services sector is to economic growth, to help accelerate its progress, International Finance Corporation (IFC) launched several initiatives to better understand the opportunities and constraints to increasing the recruitment, retention, and promotion of women. In Tanzania, for example, IFC’s finance2equal gender program is working in partnership with a selection of companies to reduce gender gaps in the financial services sector through research, peer learning, and firm-level support. Under this initiative, the study summarized in this report investigates gaps in workplace policies and practices as well as differences in the roles of women and men and makes recommendations to reduce gender gaps.